2019
DOI: 10.1111/jfbc.12899
|View full text |Cite
|
Sign up to set email alerts
|

Characterization, antioxidant, and anticancer activities of a neutral polysaccharide from Duchesnea indica (Andr.) Focke

Abstract: A neutral polysaccharide (DIP‐1) from Duchesnea indica (Andr.) Focke was obtained by hot water extraction, ethanol precipitation and chromatographic separation (DEAE‐52 cellulose anion‐exchange column and Sephadex G‐100 gel column). The physicochemical properties of DIP‐1 were elucidated by gel permeation chromatography, monosaccharide composition, Fourier transform infrared spectrometry, UV–visible spectrophotometry, scanning electron microscope and Congo red test. The results indicated that DIP‐1 was consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…The peak at 1024 cm –1 is the characteristic absorption peak of asymmetric stretching vibrations of the ether bond on the sugar ring, indicating that there are pyranose units in RYRO1 (He et al., 2021; You et al., 2021). The signal at 1623 cm –1 was the characteristic absorption of bonded water, indicating the N–H of primary amine (Xiang et al., 2019). The signal at 1398 cm –1 was contributed by the bending vibrations of C–H (Li et al., 2019; Xiang et al., 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The peak at 1024 cm –1 is the characteristic absorption peak of asymmetric stretching vibrations of the ether bond on the sugar ring, indicating that there are pyranose units in RYRO1 (He et al., 2021; You et al., 2021). The signal at 1623 cm –1 was the characteristic absorption of bonded water, indicating the N–H of primary amine (Xiang et al., 2019). The signal at 1398 cm –1 was contributed by the bending vibrations of C–H (Li et al., 2019; Xiang et al., 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The signal at 1623 cm –1 was the characteristic absorption of bonded water, indicating the N–H of primary amine (Xiang et al., 2019). The signal at 1398 cm –1 was contributed by the bending vibrations of C–H (Li et al., 2019; Xiang et al., 2019). Moreover, the pyranoside ring absorption band was observed at 878 cm –1 (C–H ring vibration) (Nejatzadeh‐Barandozi & Enferadi, 2012) and indicated a β‐glycosidic linkage (Mohammed et al., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…SEM is a commonly used method to identify the surface microstructure of polysaccharides. 16 AOHP was observed at high magnifications (2000 and 10 000 folds). Also, it showed fragmented flakes with rough surfaces (Fig.…”
Section: Characterizations Of Aohpmentioning
confidence: 91%
“…The solutions to be tested were prepared according to the method described in a previous study. 16 The final concentration of Congo red was 40 μg mL −1 , and NaOH reached 0.1, 0.2, 0.3, 0.4, and 0.5 M, respectively. Every mixture was maintained for 30 min at room temperature and scanned by a UV spectrophotometer (721 N; Shanghai Yidian, China) in the 400-600 nm range with maximum absorption wavelength transitions at different recorded NaOH concentrations.…”
Section: Purity Detectionmentioning
confidence: 94%
“…Duchesnea indica , commonly known as false strawberry, is normally found in east Asia, in particular, China and Japan. It has been reported that the leaves and whole plant exhibit anticancer [ 10 , 11 ], antioxidant [ 12 ], and immune modulatory activities [ 13 ]. There have been no studies specifically evaluating the efficacy of Duchesnea indica extract (DIE) as a therapeutic agent for sepsis.…”
Section: Introductionmentioning
confidence: 99%